Origen, evolucion y diversidad del arroz - Acevedo, M.A.=700 1 Castrillo, W.A.; Belmonte, U.C.
(Es, En)
Ilus., 27 ref.
Keywords: ORYZA SATIVA; PROCEDENCIA; TAXONOMIA; BIODIVERSIDAD; GERMOPLASMA; VENEZUELA